2000
DOI: 10.1152/ajpregu.2000.279.4.r1341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neonatal hypoxia on the development of hepatic lipase in the rat

Abstract: Increases in plasma lipids occur during hypoxia in suckling but not in weaned rats and may result from altered hepatic enzyme activity. We exposed rats to 7 days of hypoxia from birth to 7 days of age (suckling) or from 28 to 35 days of age (weaned at day 21). Hypoxia led to an increase in hepatic lipid content in the suckling rat only. Hepatic lipase was decreased to approximately 45% of control in 7-day-old rats exposed to hypoxia but not in hypoxic 35-day-old rats. Hypoxic suckling rats also had a 50% reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…We and others have previously shown that hypoxia in neonates leads to increased serum TG concentrations (9,12,18,20,29). Hypoxia may modulate the function of enzymes associated with TG synthesis and degradation (12,38).…”
Section: Discussionmentioning
confidence: 97%
“…We and others have previously shown that hypoxia in neonates leads to increased serum TG concentrations (9,12,18,20,29). Hypoxia may modulate the function of enzymes associated with TG synthesis and degradation (12,38).…”
Section: Discussionmentioning
confidence: 97%
“…It has been hypothesized that this period, characterized by diminished adrenal sensitivity to ACTH, allows for normal brain development by keeping plasma glucocorticoid concentrations at a steady level (33). Neonatal hypoxia also causes shifts in intermediary metabolism, including hyperlipidemia and fatty liver (2,6,9,13,17). Specific changes in plasma lipids may bypass the hyporesponsiveness of the HPA axis, stimulating steroidogenesis and increasing plasma concentrations of both mineralocorticoids and glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the newborn to adapt to low O 2 depends on a multitude of physiological changes. These changes include, but are not limited to, shifts in metabolic, hemodynamic, digestive, and cardiorespiratory function (2,6,10,13,14,17,21,26,35). It has also become evident that there exists a unique developmental aspect to the maturation of the adrenocortical response to stress in the neonatal rat (1,33,37,38).…”
mentioning
confidence: 99%
“…This is likely to maintain glucose delivery to the brain and heart under hypoxic conditions. Another phenomenon of particular interest is the effect of corticosterone on the development of the hepatic and exocrine pancreatic function, which we have shown is necessary to maintain neonatal hypoxic hyperlipidemia (15,16). Therefore, in addition to the clear effects of corticosterone on maintaining cardiovascular reactivity during hypoxia, the effects on intermediate metabolism in the neonatal pup are vital components in the adaptation to hypoxia.…”
Section: Perspectivesmentioning
confidence: 94%